Optimization of ionic liquids-based microwave-assisted hydrolysis of puerarin and daidzein derivatives from Radix Puerariae Lobatae extract. (1st August 2018) - Wang, Shuya; Yang, Ziwei; Peng, Na; Zhou, Jun; Yong, Xiaoyu; Yuan, Haoran; Zheng, Tao
Highlights: A novel method for hydrolysis of puerarin and daidzein derivatives has been explored. The efficiency in this work is higher than that of the conventional catalysts. The proposed approach has convenient, high practical value technique. Abstract: Ionic liquids-based microwave-assisted hydrolysis was successfully applied for hydrolysis of puerarin and daidzein derivatives from Radix Puerariae Lobatae extract. The ionic liquids with different cations and anions have been investigated, and [Omim]HSO4 was selected as catalyst. In addition, the hydrolysis parameters, including catalyst quantity, ionic liquids concentration, microwave power and microwave time, were optimized by Response Surface Methodology. The optimal conditions were as follows: 0.82 mol/L [Omim]HSO4 ; catalyst quantity, 1.42 mL; microwave time, 7 min; microwave power, 400 W. Under those condition the average hydrolysis efficiency of puerarin and daidzein derivatives was 57.93 ± 3.08%. Compared with the traditional acidic catalysts, the [Omim]HSO4 exhibited higher efficiency, which demonstrates that ionic liquids-based microwave-assisted hydrolysis was a rapid, efficient, and simple hydrolysis technique.